TEOLOGI DALAM PERSPEKTIF ISLAM DAN KRISTEN - Indra Harahap; Aprilinda M. Harahap; Neysa Vania Nasution (Studia Sosia Religia, 2022)
Religion has a belief about God (theology), because basically religion is a divine rule as a provision for its people to arrive at inner and outer happiness, both in this world and in the hereafter. Thus every religion crowns the teachings or science of divinity (theology) in their religion as the main lesson.The purpose of this study is to analyze the differences and similarities of theological concepts in Islam and Christianity. Because it is known that these two major religions are a series of religious histories that are often discussed and debated in theological studies. Then this research is able to provide a true and precise explanation of theology in both religions, namely Islam and Christianity.The methodology used in this research is qualitative with a library research design. The data taken as well as the information that the researcher uses as a source are the Al-Quran and the Bible. Coupled with the literature of opinion leaders who wrote a lot about the explanation of the teachings of the two religions in this study.This research can produce knowledge and understanding of the teachings of God in Islam and Christianity, the knowledge of God is the most basic thing in every religious teaching. It can be concluded that the similarities between the concepts of Islamic and Christian theology are studying God, Sects and the Attributes of God, while the difference between the concepts of Islamic theology and Christian theology is that Islamic theology believes that God is One and practices the value of Unity, while Christian theology believes that God is One, but it is believed that there is another God called Relative Monotheism such as God the Father Jesus Christ and the Holy Spirit.